2020
DOI: 10.1093/biolre/ioaa059
|View full text |Cite
|
Sign up to set email alerts
|

CIB4 is essential for the haploid phase of spermatogenesis in mice†

Abstract: Spermatogenesis is a complex developmental process that involves the proliferation of diploid cells, meiotic division, and haploid differentiation. Many genes are shown to be essential for male fertility using knockout (KO) mice; however, there still remain genes to be analyzed to elucidate their molecular mechanism and their roles in spermatogenesis. Calcium- and integrin-binding protein 1 (CIB1) is a ubiquitously expressed protein that possesses three paralogs: CIB2, CIB3, and CIB4. It is reported that Cib1 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 35 publications
0
4
0
Order By: Relevance
“…To sec. SPC [ 12 , 35 , 36 ]. Furthermore, we observed the upregulation of genes associated with early spermatid development ( TJP3 , TEX29 and SAXO1 ), acrosomal vesicle components ( ACRV1 ), fertilization ( PLCZ1 ) and spermatid chromatin remodeling ( TXNDC8 and CHD5 ) [ 37 39 ] in early SPT.…”
Section: Resultsmentioning
confidence: 99%
“…To sec. SPC [ 12 , 35 , 36 ]. Furthermore, we observed the upregulation of genes associated with early spermatid development ( TJP3 , TEX29 and SAXO1 ), acrosomal vesicle components ( ACRV1 ), fertilization ( PLCZ1 ) and spermatid chromatin remodeling ( TXNDC8 and CHD5 ) [ 37 39 ] in early SPT.…”
Section: Resultsmentioning
confidence: 99%
“…Enrichment analysis revealed that DMRs were involved in major male reproductive processes, including the development of testicular seminiferous tubules, spermatogonial differentiation, and meiosis. In addition, CIB2 , AK1 , FOXJ2 , PKDREJ , SLC9A3 , and TOPAZ1 genes in the hypermethylated DMRs were specifically expressed in spermatocytes and round sperm cells, regulating spermatogenesis [ 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 ]. In hypomethylated DMRs, it was found that BCL6 is associated with cell apoptosis [ 46 , 47 ], EPHA2 regulates self-renewal of SSCs [ 48 , 49 ], TAF12 regulates the transcription program of specific genes in the testes [ 50 , 51 ].…”
Section: Resultsmentioning
confidence: 99%
“…Gene CIB4 , which is strongly expressed in mouse and human testes, plays an essential role in the spermatid head. Gene CIB4 knockout (KO) mice are sterile because haploid differentiation becomes impaired ( 33 ). Knocking out the DRC1 gene in mice completely disorders the axoneme structure of sperm flagella, impairing sperm motility ( 34 ).…”
Section: Discussionmentioning
confidence: 99%